Clinical Management of Critical COVID-19 Patients: Insights from the Literature and “On the Field” Experience - Alessandri, Francesco; Bilotta, Federico; Ceccarelli, Giancarlo; Ruberto, Franco; Araimo, Fabio; Imperiale, Carmela; Pugliese, Francesco; for the PolU COVID-19 Team (Journal of Neuroanaesthesiology and Critical Care, 2020)
The recent outbreak of the coronavirus disease (COVID-19) is a health emergency all over the world. Several health care professionals are currently putting their best efforts to deal with this situation. The aim of this review is to report insights from the literature and “on the field” experience in clinical management of critical COVID-19 patients. Respiratory support varies from high flow nasal cannula (HFNC) to noninvasive and invasive mechanical ventilation, often associated with nitric oxide, prone position, and extracorporeal membrane oxygenation (ECMO). Experienced specialists have to manage the airways minimizing any contamination and virus spread. The hemodynamic management of critical COVID-19 patients requires not only an accurate fluid strategy, but also an appropriate use of vasopressors and inotropes. Various adjuvant treatments have been proposed: antiviral drugs, immunomodulators, anticoagulants, antibiotics, and nutrition.
Keywords: clinical management; COVID-19 patients; “on the field” experience